2012
DOI: 10.1177/1753193412450651
|View full text |Cite
|
Sign up to set email alerts
|

Modified Ilizarov technique for the treatment of forearm deformities in multiple cartilaginous exostoses: case series and literature review

Abstract: The aim of this study is to evaluate the results of gradual ulnar correction and lengthening using the modified Ilizarov technique for the treatment of forearm deformities in patients with multiple cartilaginous exostoses. We retrospectively reviewed 23 forearms in 16 patients. Three different types of operative procedures were performed: (1) corrective osteotomy and gradual lengthening of the ulna, (2) corrective osteotomy of the radius, and (3) excision of exostoses. We evaluated the radiographs; range of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 20 publications
3
10
0
Order By: Relevance
“…However, the necessity of operation for such deformities is still controversial, and appropriate treatment is challenging, especially for children. The core of these problems is the concern of recurrence after surgery in skeletally immature patients [ 2 , 10 , 11 ] and less restriction of daily life activities in adult patients. Stanton and Hansen [ 12 ] and Arms et al [ 13 ] suggested less aggressive corrective surgery for forearm deformities because skeletally mature patients have a good tolerance to minimal functional impairment and appearance deformity.…”
Section: Discussionmentioning
confidence: 99%
“…However, the necessity of operation for such deformities is still controversial, and appropriate treatment is challenging, especially for children. The core of these problems is the concern of recurrence after surgery in skeletally immature patients [ 2 , 10 , 11 ] and less restriction of daily life activities in adult patients. Stanton and Hansen [ 12 ] and Arms et al [ 13 ] suggested less aggressive corrective surgery for forearm deformities because skeletally mature patients have a good tolerance to minimal functional impairment and appearance deformity.…”
Section: Discussionmentioning
confidence: 99%
“…However, the necessity of operation for such deformities is still controversial, and appropriate treatment is challenging, especially for children. The core of these problems is the concern of recurrence after surgery in skeletally immature patients [2,10,15], and less restriction of daily life activities in adult patients children [8,9]. Noonan et al found that only 13% of untreated adult patients, often with varying degrees of functional de cit, had substantial pain or limitations related to their job performance [16], and patients were found adaptable and with excellent Quick DASH questionnaire responses in previous study [10].…”
Section: Discussionmentioning
confidence: 99%
“…An expectant approach is carried out for Masada type II problems if symptoms are mild and the radial head is stable. If advanced functional impairment as well as instability and pain is present, we either plan a 2-stage procedure (first levelling of the forearm bones and, later, a radial head resection—rarely) or we advocate a complex correction with indirect reduction of the radial head using a ring fixator [ 20 , 21 ]. In patients with type III deformity, we offer to remove the painful osteochondroma but counsel most patients to wait until growth is completed.…”
Section: Mo-study Group Protocolmentioning
confidence: 99%